Patients with Darier Disease Exhibit Cognitive Impairment while Patients with Hailey-Hailey Disease Do Not: An Experimental, Matched Case-control Study - Philip Curman; Johanna Bern; Linnea Sand; Martin Cederlöf; Etty Bachar-Wikström; Jakob D. Wikström (Medical Journals Sweden, 2021)
Darier disease and Hailey-Hailey disease are severe, monogenetic dermatological disorders with mutations affecting all cells, making them liable to exhibit extra-dermal symptoms. The aim of this study is to assess broad cognitive function in individuals with these diseases, using an experimental, case-control set-up comparing cognition in patients with that in healthy controls matched for age, sex and level of education. Cognition was assessed with the Cambridge Neuropsychological Test Automated Battery. Patients with Darier disease (n = 29) performed significantly poorer on 5 of the 10 key cognitive measurements, while patients with Hailey-Hailey disease (n = 25) did not perform differently from controls. The main conclusion is that patients with Darier disease exhibit significant impairment in cognitive function, which reinforces the view that Darier disease should be regarded as a disorder affecting multiple organs, and should therefore be given medical consideration, and possibly treatment, as such.